Effects of melatonin on insulin signaling and inflammatory pathways of rats with apical periodontitis - Tavares, B. S. [UNESP]; Tsosura, T. V.S. [UNESP]; Mattera, M. S.L.C. [UNESP]; Santelli, J. O. [UNESP]; Belardi, B. E. [UNESP]; Chiba, F. Y. [UNESP]; Cintra, L. T.A. [UNESP]; Silva, C. C. [UNESP]; Matsushita, D. H. [UNESP] (Wiley, 2021)
Aim: To verify the effects of melatonin supplementation on insulin sensitivity, plasma concentrations of inflammatory cytokines, insulin signalling and inflammatory pathways in the soleus (SM) and extensor digitorum longus (EDL) muscles of rats with apical periodontitis (AP). Methodology: Seventy-two Wistar rats were distributed into 4 groups: (a) control (C), (b) control supplemented with melatonin (M), (c) AP (AP), and (d) AP supplemented with melatonin (AP + M). AP was induced by pulp exposure of the maxillary and mandibular right first and second molars to the oral environment. After AP induction, oral supplementation with 5 mg kg−1 melatonin (diluted in drinking water) for 60 days was initiated. At the end of the treatment, the following were analysed: (1) plasma concentrations of insulin and inflammatory cytokines (TNF-α, IL-6, IL-1β and IL-10) using ELISA kits; (2) glycaemia using enzymatic assay; (3) insulin resistance using homoeostasis model assessment of insulin resistance (HOMA-IR) index; and (4) phosphorylation status of pp185 tyrosine, Akt serine, IKKα/β, and JNK in SM and EDL using Western blot. Analysis of variance of two or three factors was performed, followed by the Bonferroni test. P values < 0.05 were considered statistically significant. Results: AP promoted insulin resistance, significantly increased (P < 0.05) plasma concentrations of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β), significantly decreased (P < 0.05) the concentration of anti-inflammatory cytokine IL-10, impaired insulin signalling in SM, and increased IKKα/β phosphorylation status in SM and EDL. Melatonin supplementation in rats with AP improved insulin sensitivity, significantly decreased (P < 0.05) TNF-α and IL-1β, significantly increased (P < 0.05) IL-10 plasma concentrations, and changed the insulin signalling in soleus muscle and IKKα/β phosphorylation status in SM and EDL muscles. Conclusions: Melatonin is a potent adjuvant treatment for improving apical periodontitis-associated changes in insulin sensitivity, insulin signalling and inflammatory pathways. In addition, the negative impact of AP on general health was also demonstrated.
Keywords: apical periodontitis; inflammation; insulin resistance; melatonin